2020
DOI: 10.1038/s41598-020-61659-y
|View full text |Cite
|
Sign up to set email alerts
|

Short and long period growth markers of enamel formation distinguish European Pleistocene hominins

Abstract: characterizing dental development in fossil hominins is important for distinguishing between them and for establishing where and when the slow overall growth and development of modern humans appeared. Dental development of australopiths and early Homo was faster than modern humans. The Atapuerca fossils (Spain) fill a barely known gap in human evolution, spanning ~1.2 to ~0.4 million years (Ma), during which H. sapiens and Neandertal dental growth characteristics may have developed. We report here perikymata c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
0
18
0
1
Order By: Relevance
“…The combination and regional patterning of neural crest derived cells, homeobox genes, and signaling molecules are thought to play major roles in tooth specification, which correspond with the concept of developmental modules (Mitsiadis & Smith, 2006; Townsend et al, 2009). It has been suggested that it is via these distinct development regions, or modules, that evolutionary selection can operate independently on different tooth groups (McCollum & Sharpe, 2001; Modesto‐Mata et al, 2020). The changes we observed in RP between tooth types suggests that modularity may be a useful approach to understand the shifts in RP along the tooth row.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination and regional patterning of neural crest derived cells, homeobox genes, and signaling molecules are thought to play major roles in tooth specification, which correspond with the concept of developmental modules (Mitsiadis & Smith, 2006; Townsend et al, 2009). It has been suggested that it is via these distinct development regions, or modules, that evolutionary selection can operate independently on different tooth groups (McCollum & Sharpe, 2001; Modesto‐Mata et al, 2020). The changes we observed in RP between tooth types suggests that modularity may be a useful approach to understand the shifts in RP along the tooth row.…”
Section: Discussionmentioning
confidence: 99%
“…Other applications of RP within anthropology might be similarly affected. Perikymata on the external surface of teeth reflect the same time interval as RP, and as such are used to estimate the pace of lateral enamel formation as well as to assess inter population and species variation in perikymata counts (Bocaege & Humphrey, 2016; Dean et al, 2001; Dean and Reid, 2001; Guatelli‐Steinberg et al, 2005, 2009, 2014, 2018; Guatelli‐Steinberg et al, 2007; Guatelli‐Steinberg et al, 2012; Guatelli‐Steinberg & Reid, 2010; Mann et al, 1991; McFarlane et al, 2014; Modesto‐Mata et al, 2017, 2020; Ramirez Rozzi, 1993; Ramirez Rozzi & Bermudez de Castro, 2004). Furthermore, perikymata are used in the identification and timing of stress episodes evident as linear enamel hypoplasia (Bocaege et al, 2010; Cares Henriquez & Oxenham, 2020; Cunha et al, 2004; Guatelli‐Steinberg et al, 2004; Guatelli‐Steinberg et al, 2014; Hassett, 2014; Hillson, 1992; King et al, 2002; King et al, 2005; Nava, Frayer, and Bondioli, 2019; Temple, 2016; Temple et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…e dynamic effect (Dynamic Effect) gradually appeared. e form of motion animation is the design of time and space, which is beyond the static scope [22]. However, in the digital environment based on computers and networks, the new media has twoway interactive features that greatly support the new environment's interaction.…”
Section: Dynamic Effects In the Webmentioning
confidence: 99%
“…Regarding the age at death of the SH individuals, we are aware that the rate of dental tissue formation in Middle Pleistocene populations may be significantly faster than in recent populations (Modesto-Mata et al, 2020) and that there is a certain variability in recent humans concerning dental development (e.g., Braga & Heuzé, 2007;Liversidge, 2003;Tompkins, 1996). It is very possible that the age of death of immature individuals is overestimated, so the figures obtained are only indicative and should be taken with caution.…”
Section: Discussionmentioning
confidence: 97%
“…In order to estimate the chronological age of the individuals we have employed the data for the mean age of attainment of mineralization stages published by Anderson, Thompson, and Popovich (1976) for a Caucasian population. We are aware that the rate of dental tissue formation in Middle Pleistocene populations may be significantly faster than in recent populations (Modesto-Mata et al, 2020) and that there is a certain variability in recent humans concerning dental development (Tompkins, 1996). It is very possible that the age of death of immature individuals is overestimated, so the figures obtained should be taken with caution.…”
Section: Methodsmentioning
confidence: 98%